Corpos trans-tornados: um estudo sobre a(s) transexualidade(s) e o projeto de lei 5002/2013 (lei João W. Nery) - Monteiro, Anielle Oliveira (2017)
The heteronormativity, in general lines, is characterized by a normalizer regime that imposes that all people should organize their lives through the “heterosexual” model of sexuality. Such order is reproduced in the various social spheres, influencing our legal system. Transexual people today are victims of this heteronormative social order, having their fundamental rights denied by the State. It was thinking on rescuing this social minority from such marginalization that the federal deputies Jean Wyllys and Erika Kokay created the João Nery Bill, pending in the National Congress since 2013. Also known as PL Nº 5002/2013, this Bill comes up as the first federal legislation to address the gender identity rights. The objectives that guided the present study were: to analyze the historical construction of the concepts of “transsexuality” and “gender”, using a queer and post- structuralist perspective; to investigate the civilian aspects of the name change of a transsexual person as well as its consequences in the juridical and social scope; and finally, to evaluate the relevance of the role of the State as an instrument of guarantee for the access of transsexual people to surgical procedures and hormonal treatments, through the Public Health System (SUS). The methodology applied here was based on bibliographical and documentary field research and the interpretation of the data, in turn, was supported in the discourse analysis according to Michel Foucault. The research in question showed that it is of great importance to approve a federal law that contemplates the right to rectify the name of the transsexual person as well as unrestricted, free and safe access to surgical and therapeutic procedures. However, the realization of a “trans citizenship” is beyond advances in the legal field, since in Brazil there is a great chasm between the implementation of protective legislation of minority groups and the concretization of same in the daily life of the people to whom is intended.